2014
DOI: 10.1007/s40692-014-0015-9
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Social Network Sites as innovative pedagogical tools: factors and mechanism affecting students’ continuance intention on use

Abstract: Mobile Social Network Site (MSNS) is introduced into teaching and learning as a kind of innovative pedagogical tool, called MSNS-based ubiquitous learning, which allows students to learn at anytime and anywhere. Continuous use is the success of an innovative tool. Nevertheless, several previous studies have indicated factors and mechanism affecting students' continuance intention in the context of MSNS-based ubiquitous learning. In this study, a behavioral model based on "cognitionaffect-conation" framework is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…The data suggested that perceived ease of use did not affect continuous intentions, but did affect reading usefulness, which was an extra finding of the study different from the existing study [29], [30]. Therefore, it could be seen that factors influencing the continuous intentions to use e-reading APPs were related to reading usefulness, perceived ease of use, perceived risk, subjective norms and satisfaction.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The data suggested that perceived ease of use did not affect continuous intentions, but did affect reading usefulness, which was an extra finding of the study different from the existing study [29], [30]. Therefore, it could be seen that factors influencing the continuous intentions to use e-reading APPs were related to reading usefulness, perceived ease of use, perceived risk, subjective norms and satisfaction.…”
Section: Discussioncontrasting
confidence: 70%
“…Der Heijden(2004) [29] studied the continuous usage intention of users of hedonic information system and found that perceived ease of use has a positive impact on the continuous use intention, and the influence of perceived ease of use was greater than that of perceived usefulness. Wang and Du (2014) [30] introduced mobile social networking sites (MSNS) into teaching as an innovative teaching tool, proposed a behavioral model based on the framework of "cognition-emotion-identity", and found that the perceived quality in pedagogy is an important reason affecting student satisfaction and continuous use.…”
Section: Reading Usefulness Users' Satisfaction and Continuance Intmentioning
confidence: 99%
“…Once users access to Web 2.0 tools and services through their mobile devices ubiquitously, it is called mobile Web 2.0 (MW2.0; R.-B. Wang & Du, 2014). Human SIs could be revolutionized through the use of MW2.0 in that barriers of social discourse are lessened by minimizing unfamiliarity (Beach et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Current studies on exploring the conventional use of these tools for daily SIs cannot explain the behavior of individuals to adopt them for learning purposes (Tan, Ooi, Sim, & Phusavat, 2012; R.-B. Wang & Du, 2014; C.-H. Wong, Tan, Loke, & Ooi, 2015). Consequently, it is important to explore the factors that influence users to adopt mobile Web 2.0 learning (MW2.0L).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the theoretical underpinnings of reasoned action and planned behaviour (Ajzen and Fishbein, 1980;Ajzen, 1985Ajzen, , 1991 can be appropriately applied to explain firm users' behaviour in association with the assimilation of enterprise e-banking. The effect of satisfaction on continuance intention has been explored in different online services (Wang and Du, 2014;Joo et al, 2017). With regard to enterprise e-banking services, it is meaningful to find out whether firm users feel that their expectations are fulfilled through testing the mediating effect of satisfaction.…”
Section: Mediating Effect Of Satisfactionmentioning
confidence: 99%